Alveolar Soft Part Sarcoma in the Female Genital Tract: Case Series with Literature Review and SEER Database Analysis - Long X; Jiang Q; Li R; Wang D; Zou D (Dove Medical Press, 2024)
Xingtao Long,1 Qingming Jiang,2 Rengui Li,1 Dong Wang,1 Dongling Zou1 1Department of Gynaecological Oncology, Chongqing University Cancer Hospital, Chongqing, People's Republic of China; 2Department of Pathology, Chongqing University Cancer Hospital, Chongqing, People's Republic of ChinaCorrespondence: Dongling Zou, Department of Gynaecological Oncology, Chongqing University Cancer Hospital, 181 Hanyu Road, Shapingba District, Chongqing, 400000, People's Republic of China, Tel +8613657690699, Fax +8602365075612, Email cqzl_zdl@163.comIntroduction: Alveolar soft part sarcoma (ASPS) is a rare and distinct subtype of soft tissue sarcoma. This study aims to describe the unique presentation of ASPS in the female genital tract.Methods: Prognostic factors for cancer-specific overall survival (CSS) were evaluated using multivariate analyses.Results: In our case series, we identified a novel TFE3-PRCC gene fusion in a 24-year-old unmarried patient with cervical ASPS who underwent fertility-sparing surgery and remained recurrence-free for 41 months. The other two patients underwent radical hysterectomy and bilateral salpingo-oophorectomy. At the time of writing, the two patients had been disease-free for 49 and 71 months, fluorescence in situ hybridization showed break-apart signals for the ASPL-TFE3 gene. Among the 55 cases with available information from the PubMed/Medline database, most presented with localized disease, and at the last follow-up, all patients were alive and 45 patients showed no evidence of disease. The 5-year CSS rate in the female genital tract cohort from SEER database was 86.2%. Multivariate analysis revealed that older age was associated with a 1.042-fold increased risk of cancer-specific mortality (HR=1.042, 95% CI 1.022- 1.063, P < 0.001), involvement of soft tissue including the heart was associated with a 4.786-fold higher risk (HR=4.7868, 95% CI 1.681- 13.623, P= 0.003), and regional infiltration and distant metastasis were associated with approximately 8.6-fold and 18-fold higher risk of cancer-specific mortality compared to local disease, respectively (HR=8.652, 95% CI 2.529- 29.63, P = 0.001; HR=18.366, 95% CI 6.153- 54.817, P< 0.001). Patients who underwent radical excision did not show reduced cancer-specific mortality compared to those who underwent local excision (HR=0.492, 95% CI 0.224- 1.081, P = 0.078).Discussion: Previously unrecognized genetic diversity exists in ASPS. Patients with ASPS in the female genital tract have the lowest likelihood of presenting with a distant disease and are associated with a more favorable survival outcome.Keywords: ASPSCR1, TFE3, alveolar soft part sarcoma, fusion